The prevalence rate of musculoskeletal disorders among police personnel in west coast, Sabah: A preliminary investigation - Tiong, Alastair Kwan Zher; Ismail Maakip; Peter Voo Su Kiong (Academic Inspired Network, 2023)
Musculoskeletal disorders (MSDs) are one of the most serious work-related ailments. Among all the occupations, policing identified as one of the most dangerous occupations and with the highest prevalence rate of musculoskeletal disorders (MSDs). This study examined the prevalence rate and the experience of MSD based on bodily region among police officers in west coast Sabah (n=165). The questionnaires used in this study consist of demographical factors and La Trobe Musculoskeletal Disorder Questionnaire. The data was collected and analysed with the use of SPSS version 22.0. The prevalence rate of MSDs among police officers was 34.81% with male officers (25.95%) having a higher prevalence rate than females (8.86%). Among the body parts, the neck and shoulder reported the highest frequency of prevalence of MSDs, while the middle to lower back reported the highest severity of pain.